SISTEM INFORMASI MONITORING GLUKOSA DAN LAYANAN KESEHATAN TERINTEGRASI - Era Sari Munthe; Purwo Agus Sucipto (ISTEK WIDURI, 2026)
The advancement of digital technology in the healthcare sector requires systems capable of supporting real-time and integrated patient monitoring, particularly in the management of chronic diseases such as diabetes mellitus. This study aims to develop and evaluate an integrated glucose monitoring information system to enhance monitoring effectiveness and improve clinical decision-making quality. The research employs a mixed methods approach with a sequential explanatory design, combining quantitative analysis through system performance measurement and qualitative analysis through exploration of user experiences. The results indicate that the developed system demonstrates high usability, consistent data accuracy, and responsive access speed, thereby improving patient adherence to monitoring and increasing the efficiency of healthcare professionals in service delivery. Qualitative findings also reveal that the system facilitates real-time access to health information and strengthens communication between patients and healthcare providers. This study contributes to the development of an integrated and user-adaptive health information system model and offers practical implications for supporting digital transformation in technology-based healthcare services.